Intensi Berkunjung Wisatawan Domestik ke Pantai Kuta Mandalika, Lombok - Siti Anggriana; Putu Saroyini Piartrini; I Putu Gde Sukaatmadja (JURNAL MASTER PARIWISATA, 2022)
The context of this studyis that, as a result of Covid-19, the number of tourist trips has reduced dramatically. The reduction in visits suggests a reduction in intent. Attitudes, subjective norms, behavioral control, which is beginning to shift in negative way, in addition the shifting destination image owing to health hazards, all influence intentions. As a result, the goal of this study, to investigate the impact of four variables on intentions. Qualitative and quantitative data types. Primary and secondary data sources. Questionnaires, interview findings are the primary sources of information, while data from beach managers is secondary. The sample size was determined by using purposive sampling, which totaled 100 persons. PLS-SEM is data analysis technique. The findings revealed that, with t-statistic of 2.762, attitude had significant positive effect on visiting intentions, the highest original sample value being that Kuta Beach is a wonderful. Subjective norms haven’t significant positive effect on t-statistics. 0.378. Behavioral control and destination image have significant positive effect on visiting intentions with t-statistics of 2.288 and 2.319. Attitude is the most dominant variable influencing intention. There are three variables have significant positive effect on intentions, attitudes, behavioral control, and destination image. This research model is able to explain 52.8% of intention. Suggestions to the management, improve the cleanliness of the toilets, always foster the community of souvenir traders not to force tourists to buy their goods. Finally, more research is needed to undertake more comprehensive study Based on the idea of planned behavior, which includes behavioral characteristics. Keywords: attitude, subjective norm, behavioral control, destination image and intention to visit.